Comparison of Labetalol Versus Dexmedetomidine to Assess the Hemodynamic Responses to Laryngoscopy and Intubation. - Bhaskar Kuwar (Journal of Biomedical and Pharmaceutical Research, 2018)
Background and aims: During general anaesthesia, maneuver of laryngoscopy and tracheal intubation isaccompanied by varying degree of sympathetic stimulation. This may prove detrimental in patients with compromised cardiac and cerebrovascular reserve and hence many approaches have been tried to prevent the potentially adverse circulatory responses. In the present study, we compared dexmedetomidine with labetalol to assess and evaluate the haemodynamic responses to laryngoscopy and endotracheal intubationduring induction of general anaesthesia and during extubation. Material and methods: This study was carried out in ninety patients who were posted for various surgeries requiring general anaesthesia with orotracheal intubation. They were allocated into three groups. Group Dpatients received 0.5mcg/kg dexmedetomidine, diluted to 5ml of 0.9% normal saline, group L received 0.25mg/kg labetalol diluted to 5 ml normal saline and group C received 5ml 0.9%normal saline. All study drugswere administered over 5 minutes followed by induction with IV Propofol 2mg/kg and suxamethonium 1.5 mg/kg.Haemodynamic monitoring of systolic and diastolic blood pressure, heart rate(HR), mean arterial pressure(MAP) were done Results: Group D and group L showed statistically significant fall in HR,SBP, DBP, MAP RPP at induction, at intubation(I0), I1, I3, I5, I10, I15 than group C(p<0.001). There were decrease in HR, SBP, RPP in group D than in group L (p<0.001), while at I10 and I15 fall in MAP was significant in group D(p<0.001). Group C showed incidence of tachycardia and hypertension to be 83% and 77% respectively. Group D showed bradycardia in three patients and hypotension in four out of thirty patients which were statistically insignificantwhen compared to group L.(p>0.05). Conclusion: The haemodynamic responses to laryngoscopy, endotracheal intubation and extubation are better controlled with dexmedetomidine than labetalol. Keywords: Laryngoscopy, Endotracheal intubation, Haemodynamic responses, Dexmedetomidine, Labetalol.